Bahasa Inggris - Ayu Afriani Panyuwa; Rosiana Eva Rayanti; Wina Yutari; Shanda Setiawan; Fany Rahma; Even Yuanda (An Idea Health Journal, 2026)
Background: The rising prevalence of non-communicable diseases (NCDs) necessitates the development of innovative digital healthcare solutions to improve prevention and self-management. This study developed and evaluated an Android-based application for NCD prevention and management, focusing on feasibility, validity, and reliability. Methods: A research and development (R&D) approach was utilized, comprising four stages: define, design, develop, and disseminate. The application underwent expert feasibility testing with nursing experts, community specialist physicians, contextual experts, and program managers. Construct validity was determined using item-total correlation (Pearson), and reliability was assessed with Cronbach’s alpha. Additionally, a small-scale user trial with 40 participants evaluated ease of use, appearance, satisfaction, and overall usability using a 17-item Likert-scale instrument. The application achieved high feasibility, with an overall score of 86.4%. Results: All items met established validity and reliability criteria. User testing further indicated strong acceptance, favorable usability, high user satisfaction, and a positive interface evaluation. Conclusion: In summary, the Android-based NCD application is feasible, valid, and reliable for supporting the prevention and management of non- communicable diseases. Larger-scale studies are warranted to assess its effectiveness in improving health behaviors and outcomes.